Early sport specialisation, does it lead to long-term problems? - Mostafavifar, A. M.; Best, T. M.; Myer, G. D. (British Journal of Sports Medicine, 2013)
Sports participation is increasing in the USA (US population 313 million inhabitants) and in Icelandic (population 320 thousand inhabitants) adolescents, it is estimated that 35-45 million youth 6-18 years of age participate in some form of organised or recreational athletics.1 ,2 However, sports specialisation including year-round sport-specific training, participation on multiple teams of the same sport and focused participation in a single sport is purported to be increasing in frequency in preadolescent children across the world. There are several factors that contribute to the desire of young athletes to specialise in a single sport including the pursuit of scholarships or professional contracts, being labelled as talented by parents or coaches, retailing industry and media reports.3 A 2006 New York Times article notes "A growing number of coaches, parents, and children believe that the best way to produce superior young athletes is to have them play only one sport from an early age, and to play it virtually year-round."4 Despite this increase in global sports participation, physical fitness levels of children and adults are declining and more people around the globe are becoming obese and physically inactive.1 The efforts to specialise youth sports underlie the effects of reduced general opportunity for all children to participate …